AUTOLOGOUS FAT TRANSFER: CONTROVERSIES AND CLINICAL APPLICATIONS IN ORAL AND MAXILLOFACIAL SURGERY - Naik, Vinayak G.; Khandeparker, Rakshit Vijay Sinai; Berwal, Vikas; Savant, Kiran (Medico Research Chronicles, 2015)
Autologous fat transfer is a technique widely used in cosmetic surgery to correct folds of the face. Autologous fat possesses many qualities of ideal filler, including its lack of immunogenicity, abundant supply, relatively low cost and potential for durable results, however, there exists a controversy concerning the optimal donor sites, the optimal techniques of harvesting, processing, injecting fat into the recipient sites and graft survival. In recent years there has been a renewed interest and more widespread clinical use of fat grafts in Aesthetic and Reconstructive Surgery, however, the scientific literature offers very few studies when concerning its use in the maxillofacial region. The aim of this scientific review is to focus on resolving the controversies surrounding the autologous fat transfer and to highlight its possible clinical applications in the field of Oral and Maxillofacial Surgery.